2003
DOI: 10.1309/y6lpc0lr726l9dx9
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Antibodies

Abstract: The recent clinical and commercial success of anticancer antibodies such as rituximab and trastuzumab has created great interest in antibody-based therapeutics for hematopoietic malignant neoplasms and solid tumors. Given the likelihood of lower toxic effects of antibodies that target tumor cells and have limited impact on nonmalignant bystander organs vs small molecules, the potential increased efficacy by conjugation to radioisotopes and other cellular toxins, and the ability to characterize the target with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 75 publications
0
51
0
Order By: Relevance
“…1,2 In the present work, we sought to further investigate the mechanism of action of the aIGF-1R MoAb A12. Using an IGF-1/insulin-dependent hematopoietic cell line model, FD/IGF-1R, it was found that culture of the cells in IGF-1 along with the aIGF-1R A12 antibody resulted Figure 3 Flow-cytometric analysis of caspase activation following aIGF-1R A12 monoclonal antibody (MoAb) treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In the present work, we sought to further investigate the mechanism of action of the aIGF-1R MoAb A12. Using an IGF-1/insulin-dependent hematopoietic cell line model, FD/IGF-1R, it was found that culture of the cells in IGF-1 along with the aIGF-1R A12 antibody resulted Figure 3 Flow-cytometric analysis of caspase activation following aIGF-1R A12 monoclonal antibody (MoAb) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The promise of these therapies lies with the potential for a high degree of specificity in targeting malignant cells through specific antigenic determinants. Antibodies alone have limited cytotoxic effects on tumor cells, so successful use of this approach requires combination treatment with conventional chemotherapies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of those small antibody fragments are often required to enhance their affinity and avidity to targeted proteins. In recent years, monoclonal antibodies have shown increasing success as targeted anticancer and diagnostic agents (25,26), and a further search for high affinity reagents with restricted specificity to tumor-associated antigens is in progress. Historically, the hybridoma cell line specific to the antigen IL13R␣2, however, has been unavailable to the scientific community.…”
mentioning
confidence: 99%
“…This results in rather low concentrations of scFv molecules in the circulation, which in turn reduces unspecific accumulation in non-target tissues, but it also reduces the total dose localizing to the tumor (19). On the other hand, large molecules, such as whole IgGs, show poor extravasation and slower tissue diffusion (20,21). At the same time, they can exhibit prolonged serum half-lives of up to several weeks (19), because they avoid renal excretion and are instead removed by the more delayed hepatic clearance (22).…”
mentioning
confidence: 99%